Morgagni hernia accompanied by obstruction of uretero-pelvic junction in childhood - SOYLU, Hanifi; DOGRUL, Mehmet; KUTLU, N.Onur; BAYSAL, Tamer; SONMEZGOZ, Ergun; AKINCI, Aysehan (Annals of Medical Research, 2021)
None